Sorption of Bromthymol Blue with Methaemoglobin of Donor and Placental Blood in Ethylene Glycol and PEG-3000 Solutions - Kucherenko, Yu. V.; Leonov, B. N.; Rozanova, K. D. (Problems of Cryobiology and Cryomedicine, 2003)
The authors studied the sorption of bromothymol blue (BTB) by donor and placental blood haemoglobin in ethylene glycol (EG) and PEG-3000 solutions with the same value of dielectric constant, Îµs. The performed investigations show that there is no distinct correlation between Îµs and parameters of BTB sorption by methaemoglobin from donor and placental blood. In addition, the obtained data testify to the possible sorption of PEG-3000 molecules on protein surface.